The policy of Russian Federation in Asia-Pacific region: Vietnamese vector - O. T.H. Nguyen; O. E. Grishin (Проблемы постсоветского пространства)
The policy of «pivot to the East» of Russia was determined by the influence of the growing importance of the countries of the Asia-Pacific region in the world economy, as well as the need to develop the Far East and the nature of relations with the West. In this policy, the development of traditional friendship with Vietnam is a favorable condition for Russia to increase its presence in the Asia-Pacific region. The purpose determination of Vietnam’s position in Russian foreign policy in the Asia-Pacific region. The objectives traditional history of Russia-Vietnam friendship relations, assessment of the effectiveness of cooperation in the present and prospects for cooperation in the future. The study shows that based on existing traditional friendships and potential cooperation’s that need to be leveraged in the future, Vietnam is still considered an important link for Russia’s growing influence in the Asia-Pacific region.